LEGAL ANALYSIS OF THE IMPACT OF LAW NUMBER 45 OF 2009 ON UNLAWFUL FISHING ACTIVITIES IN THE NATUNA REGION - Harahap, Emirza Henderlan (ANAYASA : Journal of Legal Studies, 2024)
The aim of this research is to analyze the law regarding the impact of law number 45 of 2009 on unlawful fishing activities in the Natuna region .Researchers use normative law as their research methodology.  Normative law is a type of research that uses law as a system of norms . This norm system involves norms, rules, principles and legal regulations. Normative research is a process of finding legal rules, principles, or theories to solve legal problems. Normative research, also known as doctrinal law, is a type of research that aims to develop new theories, concepts or arguments to help solve problems . The results of this research are that many illegal fishing activities occur in the Natuna sea. Apart from that, the lack of supervision has resulted in a large number of individuals from foreign countries. So the elements resulting in illegal fishing ( fishing) in Natuna waters are as follows: very limited skills for investigators in the field of fisheries as well as TNI-AL officers and law enforcement officers in the field of maritime affairs and fisheries, as well as prosecutors and judges; lack of coordination and equality between law enforcers; lack of plans to implement law enforcement systematically and over a long period of time; lack of integrity of law enforcement, which is capable of having an impact on the process and law enforcement.